The relationship between multiple intelligences with preferred science teaching and science process skills - Samsudin, Mohd. Ali (2015)
This study was undertaken to identify the relationship between multiple intelligences with preferred science teaching and science process skills. The design of the study is a survey using three questionnaires reported in the literature: Multiple Intelligences Questionnaire, Preferred Science Teaching Questionnaire and Science Process Skills Questionnaire. The study selected 300 primary school students from five (5) primary schools in Penang, Malaysia. The findings showed a relationship between kinesthetic, logical-mathematical, visual-spatial and naturalistic intelligences with the preferred science teaching. In addition there was a correlation between kinesthetic and visual-spatial intelligences with science process skills, implying that multiple intelligences are related to science learning